Periodic solutions for a class of the second order impulsive Hamiltonian systems with mixed potential (Nonlinear Studies, 2015)
This paper is concerned with the existence of  periodic  solutions for a class of  second order impulsive Hamiltonian systems. By employing the least action principle and the Saddle Point Theorem,  We obtain sufficient conditions for existence of  periodic solutions, which generalized and improve those in the literature. The main results  are also demonstrated with examples.